ESAU’S JOURNEY OF RECONCILIATION: A HEBREW NARRATIVE APPROACH TO LEADERSHIP — FROM LOST BIRTHRIGHT TO FOUNDING A NATION - Sugihyono; Lukito, Anon Dwi (SEKOLAH TINGGI TEOLOGI DAN ENTREPRENEURSHIP PRINGGADING (STEP) SEMARANG, 2026)
This article reexamines the figure of Esau in comparison with his brother Jacob, focusing on their respective leadership strengths as narrated in Genesis 25–36. Traditionally, scholars in biblical studies and theological reflection have prioritized Jacob as the covenant patriarch who received the birthright, while Esau has been marginalized as the rejected, even forgotten, firstborn. Using a qualitative methodology that combines exegetical study, narrative analysis of the Hebrew text, and comparative leadership theory, the article examines key passages such as Esau’s reconciliation with Jacob in Genesis 33 and the genealogical establishment of Edom in Genesis 36. Jacob, by contrast, is portrayed as a leader shaped by covenantal authority and strategic maneuvering. Taken together, their lives offer two complementary paradigms of leadership—one spiritual and visionary, the other pragmatic and reconciliatory. These findings suggest that Esau should not be reduced to a lesser figure, but rather should be recognized as a model of leadership that values forgiveness, healing, and the courage to move beyond past. This reassessment not only enriches biblical leadership studies but also provides contemporary insights into balancing covenant vision with pragmatic reconciliation in leadership contexts.